Localization and Function of Early Cell Division Proteins in Filamentous Escherichia coli Cells Lacking Phosphatidylethanolamine - Mileykovskaya, Eugenia (American Society for Microbiology, 1998)
Escherichia coli cells that contain the pss-93 null mutation are completely deficient in the major membrane phospholipid phosphatidylethanolamine (PE). Such cells are defective in cell division. To gain insight into how a phospholipid defect could block cytokinesis, we used fluorescence techniques on whole cells to investigate which step of the cell division cycle was affected. Several proteins essential for early steps in cytokinesis, such as FtsZ, ZipA, and FtsA, were able to localize as bands to potential division sites in pss-93 filaments, indicating that the generation and localization of potential division sites was not grossly affected by the absence of PE. However, there was no evidence of constriction at most of these potential division sites. FtsZ and green fluorescent protein (GFP) fusions to FtsZ and ZipA often formed spiral structures in these mutant filaments. This is the first report of spirals formed by wild-type FtsZ expressed at normal levels and by ZipA-GFP. The results suggest that the lack of PE may affect the correct interaction of FtsZ with membrane nucleation sites and alter FtsZ ring structure so as to prevent or delay its constriction.